2018
DOI: 10.1016/j.ijproman.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Championing and promoting innovation in UK megaprojects

Abstract: In this article we explore the role of innovation champions and the ways innovation is championed and promoted in five selected UK megaprojects. To date, this research area is surprisingly underexplored in the megaproject management literature. The study is based on thirty interviews with innovation champions to capture their own perceptions and narratives on the ways innovation is stimulated and promoted in megaprojects, combined with relevant textual materials. Innovation was commonly defined as a step chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 39 publications
0
43
0
2
Order By: Relevance
“…Leaders who boldly pursued innovation (Hsu, 2009;Wang et al, 2018), ensured that a variety of employees and resources were brought to bear on a given challenge (Aarikka-Stenroos et al, 2017), held a tolerance for ambiguity (Koch et al, 2015;Shane et al, 2003), and, otherwise, made space temporally, attitudinally, and organizationally for innovation was effective in building the confidence of their work forces (Song et al, 2011). This mirrors findings elsewhere that transformative leadership (known colloquially as visionary leadership; Kandiko, 2013) was effective in making innovation more likely (Abbas et al, 2012;Bolderdijk et al, 2018;Sergeeva & Zanello, 2018;Y. Wang et al, 2018;Yidong & Xinxin, 2013).…”
Section: Leadership Style: the Effects Of Having Innovation Championsmentioning
confidence: 79%
See 2 more Smart Citations
“…Leaders who boldly pursued innovation (Hsu, 2009;Wang et al, 2018), ensured that a variety of employees and resources were brought to bear on a given challenge (Aarikka-Stenroos et al, 2017), held a tolerance for ambiguity (Koch et al, 2015;Shane et al, 2003), and, otherwise, made space temporally, attitudinally, and organizationally for innovation was effective in building the confidence of their work forces (Song et al, 2011). This mirrors findings elsewhere that transformative leadership (known colloquially as visionary leadership; Kandiko, 2013) was effective in making innovation more likely (Abbas et al, 2012;Bolderdijk et al, 2018;Sergeeva & Zanello, 2018;Y. Wang et al, 2018;Yidong & Xinxin, 2013).…”
Section: Leadership Style: the Effects Of Having Innovation Championsmentioning
confidence: 79%
“…Similarly, leaders or managers who supported innovation tended to take a promotion focus (playing to win; Poskela & Martinsuo, 2009 ), rather than a loss prevention focus (playing not to lose; Manimala, Jose, & Thomas, 2006 ; Poskela & Martinsuo, 2009 ), thereby taking calculated risks and enabling their followers to do the same (Bowles & Hattie, 2013 ; Koch et al, 2015 ; Maria Stock, Zacharias, & Schnellbaecher, 2017 ; Sergeeva & Zanello, 2018 ; Spanjol & Tam, 2010 ). While a majority of studies found that the effect of champions was significant, Chen, Li, and Leung ( 2016 ) pointed out that two recent meta-analyses revealed that champions only had a small effect on the quantity of innovation by individuals.…”
Section: Results For Expectancies In the Literature: Can I Do This?mentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, the KPMG review did not list “innovation” as a recommendation to improve project delivery capability. However, the recent successful implementation of early contractor engagement at Bank Station Capacity Upgrade is an example of innovation being created, practiced, and championed within the same organization (Sergeeva & Zanello, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Megaprojects in centralized management models of the national economy limit the independence of organizations in decision-making, create conditions incompatible with the system of "creative destruction", and limit the entrepreneurial potential of the business. More details about supporting and promoting innovation in UK megaprojects can be found in [5].…”
Section: Resultsmentioning
confidence: 99%